POLISEMIYA HÁM OMONIMLERDIŃ ULÍWMALÍQ BELGILERI HÁM ÓZGEShELIKLERI - Orazımbetov, A.Q. (ILIM hám JÁMIYET, 2025)
The article examines modern linguistics’ approaches to the phenomenon of polysemy and homonymy at different levels of the language system.